Microstructure and corrosion resistance of radial friction welded supermartensitic stainless steels. Issue 7 (2nd July 2016) - Della Rovere, Carlos Alberto; Ribeiro, Celso Roberto; da Silva, Rodrigo; de Alcântara, Nelson Guedes; Kuri, Sebastião Elias
Abstract: In this work, supermartensitic stainless steel pipes were radial friction (RF) welded and their corrosion behaviours were studied based on potentiodynamic polarisation and double-loop electrochemical potentiokinetic reactivation tests. Measurements were performed on samples taken from the base metal (BM), weld interface and consumable ring (CR) of the RF weldment. The corrosion properties are discussed in terms of their resulting metallurgical microstructure. The precipitation of Cr carbides that takes place during the tempering treatment induces a substantial Cr depletion value ( I r / I a  = 54.22%). On the other hand, CR and weld interface regions, which had their microstructure transformed and their Cr carbide precipitates redissolved by the RF welding thermomechanical cycle, present a low level of Cr depletion ( I r / I a  < 1%). The AC microstructure, which is composed of a mixture of virgin martensite and stable retained austenite, presents an increase in pitting corrosion resistance compared to the tempered structure of the BM region. It was also observed that the δ-ferrite decreases the pitting resistance of the weld interface region.